ANALISIS PERHITUNGAN HARGA POKOK KAMAR HOTEL DENGAN MENGGUNAKAN METODE ACTIVITY BASED COSTING (ABC) (Studi Kasus: Swiss Belhotel Borneo Samarinda) - Retno Maninggar Jati; Yulius Gessong Sampeallo; Yustika Nur Amalia (Politeknik Negeri Samarinda, 2019)
Majority of hotels still use conventional methods in determining their costs. If the conventional accounting method is not changed, there will be a gap between the information needed by management to face competition between companies, because conventional accounting methods do not provide accurate information in its application. The purpose of this study is to get more accurate results from the activity based costing method in calculating costs regarding hotel room rates. The results showed that the calculation of hotel room rates using the cost-based activity method showed that the tarif was lower than the rate applied by the hotel in all types of rooms due to the overhead of each product. On activity-based costing, overhead costs for each product are charged to many cost drivers. Related to cost-based activities can allocate activity costs to each type of room at Swiss Belhotel Borneo according to the needs of each activity. Keywords: activity based costing, cost driver, Swiss Belhotel Borneo Samarinda